KECEMASAN DAN MEKANISME PERTAHANAN DIRI ALICE HOWLAND DALAM NOVEL STILL ALICE KARYA LISA GENOVA - ADELIN, GLEDYS (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT The research is entitled â€œKecemasan dan Mekanisme Pertahanan diri Alice Howland dalam Novel Still Alice karya Lisa Genovaâ€. There are fifteen characters in this novel but only the major character and her anxiety with defense mechanism that become the main focus in thisÂ research. The main purpose of this research is to analyze Aliceâ€™s Anxiety and Defense mechanism that are shown in the novel. In terms of methodology, the combination of two approaches are applied namely the intrinsic and extrinsic ones. The theories by Robert Stanton (2007) and Edgard Robert (1964) are used to analyze the main characterâ€™s personality. Freudâ€™s psychoanalysis is used to analyze the main characterâ€™s anxiety and defense mechanism, C. George Boereeâ€™s book entitled Personality Theory (2006) are used in this research. The research uses descriptive method and the data were collected from the novel with supporting data from some articles on the internet about anxiety and defense mechanism. After analyzing the personality of the major character, the writer finds that Alice Howland has two types of anxiety that are neurotic anxiety and moral anxiety. Alice also has some defense mechanisms: which are projection, displacement, turning against the self, rationalization, denial, compensation, and reaction formation. Keywords; Anxiety, Defense Mechanism, major character, psychoanalysis